The Benefits of Accounting Information On The Intention of Stocks Selections In Indonesia Stock Exchange (IDX) - Mf. Arrozi Adhikara; Maslichah Maslichah; Nur Diana (The Indonesian Journal of Accounting Research, 2017)
Abstract: This research objective is to both examine and provide empirical evidence concerning analysts' decision-making intentions in choosing stocks at the Indonesian stock exchange by using accounting information. This research uses a causal-explanatory approach in examining the analysts' intentions on selecting stocks. This research uses primary data with questionnaire-surveys and adopts single study. In explaining the analysts’ intentions, this research uses a causal-explanatory approach. This research shows that the benefits of accounting information (1) positively affect beliefs revisions; (2) positively affect unsystematic risk perceptions; (3) positively affects the intention of stock selections; (4) positively affect the intention of stock selections; (5) positively affect the intention of stock selections; (6) negatively affects the intention of stock selections; and (7) positively affect the intention of stock selections.  Further, this research also finds that securities analysts behaved sophistically in analyzing accounting information for decision-making purposes. Accounting information has characteristics (i.e., relevant, reliable, and fair) that in alignment with the interests of its users. The intention for stock selection is driven by the knowledge and experiences of both the respondents as well as other people. This condition shows that there is a halo effect surrounding the intention for stock selections that come from people that other than respondents (e.g., respondents' colleagues). Therefore, securities analysts tend to act prudence, sophisticated, volitional, and risk neutral.Abstrak: Tujuan penelitian ini adalah untuk menguji dan memberikan bukti empiris tentang niat pengambilan keputusan analis dalam memilih saham di bursa efek Indonesia dengan menggunakan informasi akuntansi. Penelitian ini menggunakan pendekatan kausal-explanatory dalam menguji niat analis untuk memilih saham. Penelitian ini menggunakan data primer dengan survei kuesioner dan mengadopsi studi tunggal. Dalam menjelaskan niat analis, penelitian ini menggunakan pendekatan penjelasan kausal. Penelitian ini menunjukkan bahwa manfaat informasi akuntansi (1) secara positif mempengaruhi revisi keyakinan; (2) secara positif mempengaruhi persepsi risiko yang tidak sistematik; (3) secara positif mempengaruhi niat pemilihan saham; (4) secara positif mempengaruhi niat pemilihan saham; (5) secara positif mempengaruhi niat pemilihan saham; (6) secara negatif mempengaruhi niat pemilihan saham; dan (7) secara positif mempengaruhi niat pemilihan saham. Selanjutnya, penelitian ini juga menemukan bahwa analis sekuritas berperilaku secara canggih dalam menganalisis informasi akuntansi untuk tujuan pengambilan keputusan. Informasi akuntansi memiliki karakteristik (yaitu, relevan, andal, dan adil) yang selaras dengan kepentingan penggunanya. Niat untuk pemilihan saham didorong oleh pengetahuan dan pengalaman baik dari responden maupun orang lain. Kondisi ini menunjukkan bahwa ada efek halo yang mengelilingi niat untuk pemilihan saham yang berasal dari orang-orang yang selain responden (misalnya, rekan responden). Oleh karena itu, analis sekuritas cenderung bertindak bijak, canggih, kehendak, dan risiko netral.